METHODIC PRINCIPLES OF FILLING-IN FOREARM BONE DEFECTS USING TECHNOLOGIES OF TRANSOSSEOUS OSTEOSYNTHESIS - D. Y. Borzunov; M. N. Sokolova (Travmatologiâ i Ortopediâ Rossii, 2016)
The article is based on treatment experience of 93 patients with defects and pseudoarthroses of forearm bones using transosseous osteosynthesis. The work presents main methodic principles and approaches to rehabilitation of patients using closed transosseous osteosynthesis and surgical lengthening of bone fragments.